Estudio sobre la amplitud del movimiento articular de la rodilla en el proceso de marcha de niños con parálisis cerebral espástica - Batistela, R. A. [UNESP]; Kleiner, A. F R [UNESP]; Sánchez-Arias, M. D R [UNESP]; Gobbi, L. T B [UNESP] (Elsevier, 2011)
Introduction: To analyze the contribution of knee range of motion in walking of hemiplegic and diplegic children, considering their asymmetries. Material and method: Twelve children, 6 hemiplegics and 6 diplegics, from 7 to 12 years of age (9.5 ± 1.93) participated. Spasticity was assessed with the Ashworth's Modified Scale and the passive knee range of motion using an electrogoniometer. The task was to walk on an 8 m long walkway, using their preferred speed. Six attempts were made, three of which were on the right and three on the left sagittal planes. Results: The Mann-Whitney's U test found differences in the type of cerebral palsy for knee extension/hyperextension, for the relative angle of the knee at the load acceptance phase and for the knee range of motion during stride. The Wilcoxon's test revealed differences in hemibody for hemiplegics in the relative angle of the knee in acceptance of the load. Conclusions: Children with spastic cerebral palsy use compensation strategies between the lower limbs during walking. These strategies differed according to the type of cerebral palsy. The knee joint has an important function in those strategies, especially in the load acceptance and propulsion phases. © 2010 Elsevier España, S.L. y SERMEF. Todos los derechos reservados.
Study on the range of movement in the joint of the knee in the walking process in children with spastic cerebral palsy
Keywords: Gait; Knee; Range of motion; Spastic cerebral palsy